Evaluation of microalgae’s plastic biodeterioration property by a consortium of chlorella sp. and cyanobacteria sp. - Natanamurugaraj, Govindan; Bhuyar, Prakash; Feng, Ho Xuan; Mohd Hasbi, Ab. Rahim; Maniam, Gaanty Pragas; Sundararaju, S.; Muniyasamy, S. (Kauno Technologijos Universitetas, 2021)
Malaysia is one of the top eight countries that has a drawback of mismanaged plastic waste. This study intended to investigate polymer degradation using the biological technique with the help of microalgae to minimise the time required for biodegradation. This research article aims to identify the collected sample with the most suitable microalgae for the biodegradation of microplastic and to analyse the biodegradation of the polymer by microalgae. The results revealed that the consortium of Chlorella sp. and Cyanobacteria sp. were able to deteriorate low-density polyethene (LDPE sample) through several stages, and this was confirmed by UV-Spec, FESEM, EDX, CHNO, FTIR and DSC analysis. The results obtained revealed that microalgae producing exopolysaccharides (EPS) decreased the carbon and oxygen ratio. According to SEM micrographs, microalga may colonise, agglomerate, and adhere microplastics to its surface, regardless of its fractional size. The EDX analysis showed that the initial composition of carbon was 92.30±1.23%, while after the incubation, the carbon composition started decreasing from 53.18% to 39.12±1.08%. Finally, there was a 37.91% decrease in carbon weight from elemental analysis.